2020
DOI: 10.1016/j.cegh.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics: Need for new fences”, a prospective utilization evaluation of cephalosporin's and its combination in tertiary care referral hospital

Abstract: Background:The cephalosporins are a large group of related β-lactam antimicrobial agents with broad spectrum of activity. Drug Utilization and Evaluation (DUE) is an ongoing, structured process to analyse the pattern of drug administration in various practice settings, including hospitals in relation to guidelines or predetermined standards thereby promoting the appropriate and effective use of drugs. Methods: This prospective interventional study was conducted for a duration of six months among the in-patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Out of 137 patients, only 4 patients (3%) were started with cefotaxime. A study conducted in Trinidad found that 26.5% of patients were started with cefotaxime (Pinto Pereira et al, 2004) and only 1% of patients was started with cefotaxime in India (Chandrasekhar et al, 2020). Up until today, no other studies that research the use of thirdgeneration cephalosporins state the specific use of cefotaxime and other antibiotics under third-generation cephalosporins.…”
Section: Amongmentioning
confidence: 99%
“…Out of 137 patients, only 4 patients (3%) were started with cefotaxime. A study conducted in Trinidad found that 26.5% of patients were started with cefotaxime (Pinto Pereira et al, 2004) and only 1% of patients was started with cefotaxime in India (Chandrasekhar et al, 2020). Up until today, no other studies that research the use of thirdgeneration cephalosporins state the specific use of cefotaxime and other antibiotics under third-generation cephalosporins.…”
Section: Amongmentioning
confidence: 99%